The Interconnection between Students and Mursyids: A Study of the Book Al-Anwār al-Qudsiyyah by Sheikh Abdul Wahab Asy-Sya'rani - M. Naufal Aulia Zein; Abrar M. Dawud Faza (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article aims to discuss the interconnection between students and mentors as described in the book al-Anwār al-Qudsiyyah by Sheikh Abdul Wahab Asy-Sya'rani. This is based on the relationship between students and mentors in the Sufi tradition, which is not only pedagogical, but also spiritual and existential. Asy-Sya’rani’s al-Anwār al-Qudsiyyah serves as an important reference for understanding the dynamics of this interconnection. Through a qualitative descriptive-analytical approach to the text, this article explores the model of the relationship established between the disciple and the spiritual guide, including ethical dimensions, spiritual hierarchy, and inner growth. The study’s findings indicate that this relationship is based on the principle of spiritual connection (ittishāl rūḥānī), which emphasizes the disciple’s total devotion (khidmah) and the spiritual responsibility of the mursyid. Additionally, it was found that Asy-Sya’rani emphasizes the importance of etiquette as the primary foundation in this relationship, which serves as the key to effectively transforming the disciple’s religious experience into a complete spiritual awareness. This article contributes to enriching the body of knowledge on tarekat practices by highlighting how classical texts such as al-Anwār al-Qudsiyyah remain contextual in addressing contemporary challenges, particularly in maintaining the continuity of Islamic spiritual traditions amid crises of authority and the fragmentation of religious identity.